(untitled) (Letras, 2019)
The recent discoveries regarding Lorenzo de Padilla’s work, which have come into light as a result of our investigation and Charles Faulhaber’s (2016) contribution, led us to formulate new questions about this author who has been systematically disregarded by his contemporaries and by specialists on the period as well. With the exception of his Catálogo de los Santos de España, the rest of his vast work on history, geography, law, and genealogy has been highly questioned and therefore forgotten. In the present work we shall first define the characteristics of his Crónicas according to its two oldest versions and then propose that the Bancroft Library’s manuscript transmits the earliest versions of the two. Moreover, we shall examine the collection of Latin epigrams included in the manuscript BNE 2775 (ff. 141r-161v), which represented a pioneer contribution to the development of archeology within the Hispanic field, seeking to explain the role it played within the text.